A weak Galerkin method for diffraction gratings. Issue 2 (25th January 2017) - Zhang, J. C.; Zhang, K.; Li, J. Z.; He, Z. B.
Abstract : This paper concerns a weak Galerkin method (WGM) for the diffraction of a time-harmonic incident wave impinging upon a one-dimensional periodic grating structure. The existence and uniqueness of the weak Galerkin solution to the grating problem are established using a variational approach. The convergence rate of the proposed WGM is systematically analyzed. Numerical simulations are presented to verify the efficiency of the WGM for solving grating problems.